Investigating the Mediating Role of Intellectual Capital in the Relationship Between Production, Process and Administrative Innovation Capabilities with Organizational Performance in Payame Noor University of Shiraz - Homa Maasomi; Hassan Soltani; Abbas Babaei Shahr Abad; Mehdi Mohammad Bagheri; Sanjar Salajeghe (مطالعات مدیریت و توسعه پایدار, 2023)
In this study, a comprehensive model has been adopted to investigate how innovation capabilities affect organizational performance and how the mediating effect of intellectual capital has also been considered. Thus, the aim of this research is to investigate the effect of production, process and administrative innovation capabilities on organizational performance, considering the mediating role of intellectual capital of Payame Noor University, Shiraz center, which is using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) Was performed. The elements of innovation capabilities analysis include production capabilities, process capabilities, and administrative capabilities. The results showed that production capabilities, process capabilities, and administrative capabilities have positive effects on intellectual capital in Payame Noor University, Shiraz Center. The impact of intellectual capital on organizational performance has been significant. In sum, intellectual capital has a mediating effect on the relationship between innovation capabilities (production, process and administrative) and organizational performance in Payame Noor University, Shiraz Center. Intellectual capital is a mediating effect between innovation capabilities and organizational performance that aim to increase organizational performance.